2015
DOI: 10.3189/2015aog69a001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased fresh water from Antarctic ice shelves on future trends in Antarctic sea ice

Abstract: Observations show that, in contrast to the Arctic, the area of Antarctic sea ice has increased since 1979. A potential driver of this significant increase relates to the mass loss of the Antarctic ice sheet. Subsurface ocean warming causes basal ice-shelf melt, freshening the surface waters around Antarctica, which leads to increases in sea-ice cover. With climate warming ongoing, future mass-loss rates are projected to accelerate, which has the potential to affect future Antarctic seaice trends. Here we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 28 publications
(51 reference statements)
1
84
4
Order By: Relevance
“…The reduction in sea ice and increase in upper-ocean temperature for all the warming cases (Figs. 5a,c) is in contrast to recent observations showing increased ice production around Antarctica (Parkinson and Cavalieri 2012;Bintanja et al 2013;Turner et al 2013;Blunden et al 2014) and an ongoing cooling trend of Southern Ocean surface waters (e.g., Latif et al 2013;Fan et al 2014). Mechanisms driving these observed trends are poorly understood.…”
Section: A Surface and Sea Ice Responsecontrasting
confidence: 51%
See 2 more Smart Citations
“…The reduction in sea ice and increase in upper-ocean temperature for all the warming cases (Figs. 5a,c) is in contrast to recent observations showing increased ice production around Antarctica (Parkinson and Cavalieri 2012;Bintanja et al 2013;Turner et al 2013;Blunden et al 2014) and an ongoing cooling trend of Southern Ocean surface waters (e.g., Latif et al 2013;Fan et al 2014). Mechanisms driving these observed trends are poorly understood.…”
Section: A Surface and Sea Ice Responsecontrasting
confidence: 51%
“…Increased heat and freshwater fluxes increase the strength of the upper-ocean stratification, hindering the onset and strength of deep convection and hence the flux of warm waters brought to the surface. Indeed, many modeling studies simulating increased surface freshwater fluxes around Antarctica produce cooling of surface waters (Aiken and England 2008;Trevena et al 2008;Swingedouw et al 2009;Ma and Wu 2011;Bintanja et al 2013Bintanja et al , 2015Morrison et al 2015). While our results produce no significant change in SST as a result of increases in runoff and precipitation (not shown), the upper 200 m does illustrate a cooling trend for the runoff cases (Fig.…”
Section: A Surface and Sea Ice Responsecontrasting
confidence: 44%
See 1 more Smart Citation
“…The results presented in this study leave open some important scientific questions, which deserve future investigation. Most importantly, the wind‐driven ocean dynamics identified in this study should work in concert with various other mechanisms identified in earlier studies, particularly wind‐driven sea‐ice transport [ Holland and Kwok , ] and cold and warm‐air advections linked to the IPO, AMO, and SAM [ Purich et al ., ; Meehl et al ., ; Clem and Renwick , ; Li et al ., ] and warming‐induced surface freshening [e.g., Bintanja et al ., ; de Lavergne et al ., ; Bintanja et al ., ; Zhang , ]. A more consistent and thorough mechanism will emerge when all the key factors and their interactions are considered together.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Information about the water balance components of lakes allows for the evaluation of a freshwater inflow into the sea due to seasonal snow melting. This could be useful for regional oceanographic models, since uncertainties in the inflow estimates may lead to significant model errors (Jenkins et al, 2001;Bintanja et al, 2015). There are only a few studies of the surface freshwater inflow in Antarctica, and they are devoted only to glacial melting (McConchie and Hawke, 2002;Dominguez and Eraso, 2007;Doran et al, 2008).…”
Section: The Fildes Peninsulamentioning
confidence: 99%